Hill- Piper diagram for drinking water quality in Ingessana area - Blue Nile State, Sudan. - A. H. Adam, Youseif.; Babiker, Mohammed Osman; Abass, Fatah Elrahaman (Gezira Journal of Engineering and Applied Sciences, 2018)
This study, aims to assess the effect of mineralization on drinking water quality and its visages in Ingessana area, which is located in the southwestern part of the Blue Nile State (Sudan). Forty drinking water samples from various sources in the study area were collected during four seasons, and then analyzed, using atomic absorption spectrometer, Flame photometer, UV spectrophotometer and conventional titration methods. Different computer software's were used to interpret data as Aquachem. The results showed that calcium, and magnesium, were the main predominant cations in the samples, while bicarbonate and chloride were the dominant anions in wet and dry seasons. Calcium, magnesium and bicarbonate are due to the presence of marble, calcite CaCO3, dolomite CaCO3, Mg (CO 3 ), aragonite, gabbros, and schist in under saturated state. Calcium chloride and bicarbonate indicate the presence of dolomite, aragonite, halite (NaCl), magnsite, gypsum and carbonate rocks as an interfere layers in the study area. These minerals occur in the fractured zone in study area. The Hill-Piper result shows that, all groundwater visages in wet seasons are normal earth alkaline and alkaline with prevailing bicarbonate, while in dry season is earth alkaline with increased portion of alkalis in water and the processes that control these visages are ion exchange and simple dissolution or mixing processes. Comparing the results with (WHO) standard, calcium, magnesium and lead are of higher levels than (WHO) drinking water standard. This may be due to mineralization in the study area. There is an impossibility to determine the effect of these augment on native's health, because most of them are medicated by traditional medicines.  As a final result most of drinking water in the area of study needs treatment before use .